SIMILE DALAM AL-QUR’AN JUZ 27 (KAJIAN STILISTIKA) (Universitas Negeri Semarang, 2022)
A simile is an expression that indicates one has something in common with others in character, either overtly or covertly, by comparing it with the furniture. In Quran juz 27 there are various types of similes. In Al-Qur'an Juz 27, there are 4 cases: what sentences have simile elements in Al-Qur'an Juz 27, simile components in Al-Qur'an Juz 27, and types of two ends of similes in Al-Qur'an Juz 27, and types of simile in Al-Qur'an juz 27. The objectives that need to achieve in this research are to find the sentences containing simile/tasbeeh elements in Al-Qur'an juz 27, to know the simile/tasbeeh components in Al-Qur'an juz 27, to understand the types of two-ended simile/tasbeeh in Al-Qur'an chapter 27, and to know the kinds of simile/tasbeeh in Al-Qur'an juz 27. This research is qualitative research with a library research design. The data collecting process is done by applying the documentation technique. The research instruments used are data cards and recapitulation. In analyzing the data, the distributional method (metode Agih) is applied. Based on the research that has been done by the researcher, 15 simile sentences were found in the Al-Qur'an Juz 27. The researcher apprehended the whole data. Based on the type of two-ended simile, there are three types analyzed. (1) based on hissi and 'aqli, (2) based on mufrod and murokkab, (3) based on the numbers. Based on hissi and 'aqli, there are 8 basic data of similes in the form of hissi similes (hissiyaani), and 7 basic data of 'aqli similes form of hissi similes. According to mufrod murokkab, there are 1 data of mufrod muthlaq simile, 5 murokkabaani similes, 6 base data of mufrod similes in murokkab. Based on the numbers, no data was found. There are four types of similes analyzed based on their presence or absence: (1) the presence or absence of simile content, (2) the presence or absence of simile furniture, (3) the absence of simile content and furniture, and (4) unique similes. Based on the presence or absence of simile content, there are 12 data of mujmal simile and 1 data of mufashal simile, which also counts as ghoiru tamtsil simile. Based on the presence or absence of the furniture of simile, there exist 13 data of mursal similes. Based on the absence of simile content and furniture, there are 2 data found on baligh similes. No unique simile data was found.